Treatment of bimaxillary protrusion using intra- and extra-alveolar miniscrews associated to self-ligating brackets system - Henrique Mascarenhas Villela (Dental Press Editora, 2020)
ABSTRACT Introduction: Moderate and severe bimaxillary protrusion impair the passive lip sealing and the facial and smile esthetics. The extraction of premolars can be avoided by the use of skeletal anchorage to retract both dental arches. This approach brings many advantages such as: prevents premolars extraction; simplifies orthodontic mechanics; there is no volume reduction of a premolar when smiling; control of overbite and gingival exposure. The utilization of this therapeutic approach, when associated with self-ligating brackets, can bring the possibility of spacing the appointments without damage to the treatment efficiency, and allows selection of the most appropriate torque prescriptions for each case. The intra-alveolar miniscrews are indicated for mild cases of bimaxillary protrusion, while extra-alveolar miniscrews may also be indicated for more severe cases. Objective: To report the treatment of three cases of mild, moderate and severe bimaxillary protrusion, in which intra- and extra-alveolar miniscrews were used, according to the retraction required. Conclusion: The retraction of both upper and lower dental arches using orthodontic intra- and extra-alveolar miniscrews, associated with self-ligating brackets, is an excellent tool to correct mild to severe bimaxillary protrusion, thus reducing the need of premolar extraction and simplifying the orthodontic management.